Synthesis and characterization of new push-pull anthraquinones bearing an arylthienyl-imidazo conjugation pathway as efficient nonlinear optical chromophores - Batista, Rosa Maria Ferreira (2010)
Compounds 1 were synthesized, in good to excellent yields (72-87%), through condensation of formyl-arylthiophene precursors 2 with 1,2-diaminoanthraquinone in ethanol at reflux, followed by cyclisation of the imine intermediate with Pb(OAc)4 in acetic acid at room temperature. Evaluation of the thermal, linear and NLO properties of these compounds was carried out. The beta values of chromophores 1, measured by hyper-Rayleigh scattering (HRS) technique, are several times larger (49-67) than that of the standard reference molecule p-nitroaniline (pNA). Due to their excellent thermal stability, (Td = 341-446 oC), and good NLO properties, arylthienyl-imidazo-anthraquinones 1 could be used as new efficient and thermally stable NLO materials.